Self-expandable metal stents as definitive treatment for esophageal variceal bleeding - Holster, I. L.; Kuipers, E. J.; van Buuren, H. R.; Spaander, M. C. W.; Tjwa, E. T. T. L. (Endoscopy, 2013)
The use of self-expandable metal stents (SEMS) has occasionally been described for the treatment of uncontrollable esophageal variceal bleeding (EVB) as a bridge to an alternative treatment option (i. e. transjugular intrahepatic portosystemic shunt [TIPS]). It is currently not known whether SEMS placement is appropriate for more than temporary hemostasis. This case series report describes five patients in whom EVB could not be controlled with variceal band ligation and who were not suitable to undergo a TIPS procedure at the time of bleeding. SEMS were placed in these patients with the intent of definitive treatment. Successful initial hemostasis was achieved in all five patients, and sustained hemostasis occurred in four. Stents were removed from two patients after > 14 days and remained in situ until death in three other patients (range 6 – 214 days). No complications related to this longer duration were observed. In one case, TIPS could be performed at a later stage. SEMS could be a definitive treatment for uncontrollable esophageal bleeding in patients with a limited life expectancy or those unsuitable for TIPS at the time of bleeding.